Reveals the Dynamic Portrait of CLIL: Breakthrough in Arabic Language Learning at the Islamic Boarding School Daarul Ukhuwah for Girl 2 Malang / Menguak Potret Dinamis CLIL: Terobosan Pembelajaran Bahasa Arab di Pondok Pesantren Darul Ukhuwah Putri 2 Malang - Wardiyatul Husna; Faisal Mahmoud Adam Ibrahim; Zakiyah Arifa (Loghat Arabi : Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2025)
This article aims to reveal the dynamics and breakthroughs in the application of the Content and Language Integrated Learning (CLIL) approach in learning Arabic through Islamic studies at the Darul Ukhuwah for Girl 2 Malang. The focus of this study is directed at how the integration of Islamic content and Arabic language learning forms meaningful, functional, and encouraging students' language skills as a whole. This study uses a qualitative approach with a case study method. Data collection techniques are carried out through observation, in-depth interviews, and documentation that are analyzed in a descriptive-qualitative manner. The main informants consisted of KMI staff, Arabic teachers, Islamic studies teachers, and students. The main findings of this study show that the application of CLIL dynamically is able to improve students' listening and reading skills in understanding Arabic Islamic texts, as well as functional and scientific speaking and writing skills. CLIL also encourages intrinsic motivation and autonomy in learning Arabic, supported by a boarding school environment that implements language zone policies, muhadatsah habituation, and classical book learning. On the other hand, challenges such as language skills variations and media limitations are addressed through adaptive strategies such as simplification of language input and teacher training. The main argument of this article is that the CLIL approach is not only relevant to the learning context in formal schools, but also very effective in boarding school environments with the power of integrating Islamic content and lively language practices.Abstrak: Artikel ini bertujuan untuk mengungkap dinamika dan terobosan penerapan pendekatan Content and Language Integrated Learning (CLIL) dalam pembelajaran Bahasa Arab melalui studi keislaman di Pondok Pesantren Darul Ukhuwah Putri 2 Malang. Fokus kajian ini diarahkan pada bagaimana integrasi konten keislaman dan pembelajaran bahasa Arab membentuk pembelajaran yang bermakna, fungsional, serta mendorong keterampilan berbahasa santri secara menyeluruh. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus. Teknik pengumpulan data dilakukan melalui observasi, wawancara mendalam, dan dokumentasi yang dianalisis secara deskriptif-kualitatif. Informan utama terdiri dari staf KMI, guru Bahasa Arab, guru studi keislaman, dan santriwati. Temuan utama dari penelitian ini menunjukkan bahwa penerapan CLIL secara dinamis mampu meningkatkan keterampilan menyimak dan membaca santri dalam memahami teks-teks keislaman berbahasa Arab, serta keterampilan berbicara dan menulis secara fungsional dan ilmiah. CLIL juga mendorong motivasi intrinsik dan otonomi belajar bahasa Arab, didukung oleh lingkungan pesantren yang menerapkan kebijakan zona bahasa, pembiasaan muhadatsah, dan pembelajaran kitab klasik. Di sisi lain, tantangan seperti variasi kemampuan bahasa dan keterbatasan media diatasi melalui strategi adaptif seperti penyederhanaan input bahasa dan pelatihan guru. Argumentasi utama artikel ini menegaskan bahwa pendekatan CLIL tidak hanya relevan untuk konteks pembelajaran di sekolah formal, tetapi juga sangat efektif di lingkungan pesantren dengan kekuatan integrasi konten keislaman dan praktik bahasa yang hidup.